Surface decorated quantum dots: Synthesis, properties and role in herbal therapy - Baig, Mirza Shahed; Suryawanshi, Ravikiran Maheshrao; Zehravi, Mehrukh; Mahajan, Hitendra S.; Rana, Ritesh; Banu, Ahemadi; Subramanian, Muthukumar; Kaundal, Amit Kumar; Puri, Sachin; Siddiqui, Falak A.; Sharma, Rohit; Khan, Sharuk L.; et al. (Frontiers in Cell and Developmental Biology, 2023)
Quantum dots are the serendipitous outcome of materials research. It is the tiny carbonaceous nanoparticles having the diameter in between 1-10 nm. This review is a brief discussion of synthesis, properties, and the biomedical applicability of quantum dots especially in herbal therapy. As quantum dots are highly polar, it can be surface decorated with several kinds of polar functionalities, polymeric molecules, small functional molecules, and so on. The review also consists of the basic physical and optical properties of quantum dots and their ex-citation dependent properties in the application section. We cover the area of therapeutics where the quantum dots were utilized as drugs or imaging probes. Nanoprobe for several diagnostics is quite new in biomedical research domain. Quantum dots based nanoprobes are on-demand due to their excellent fluorescence, non-bleaching nature, biocompatibility, anchoring feasibility to several analytes, and fast point-of-care sensibility. Lastly, we also included a discussion on quantum dots-based drug delivery as phytomedications.